The Impact of Responsible Investment on the Banking Performance in the small and medium Banks - Mekhur , Hanan Ghanim (South Asian Journal of Social Sciences and Humanities, 2024)
The purpose of the study is to study the impact of responsible investment on the banking  performance in the small and medium banks. This study used the secondary data by using  129 banks from 2018 t0 2023 and the OLS are utilised as a regression. The study utilized the  statistical software STATA to test the relation among the variables. We found a positive and  significant correlation between the responsible investments on the banking performance.  Finally, appropriate recommendations were presented to improve the quality responsible  investment on the banking performance in Asian Banks. The study concluded that the impact  of investment on the performance of banks utilizing the statistical analysis program shows  that there is a statistically important influence of investment on the bank performance of the  financial institution. Hence, it is the responsibility of the institution to distinguish among the  several investment options, with the goal of starting an investment construction in the  institution that is composed and in accordance with the economic limits, and capable of  enhancing its goals. In light of the findings extended, the study obtainable a number of  references, the most significant of which is the essential for banks in specific and firms in  overall to strengthen investment processes in the field of information technology payable to  its significance in enhancing services and raising bank performance. The findings of the study  will support decision-makers recognize the significance of investment part. The next are the  most significant results. We find that the values of banks' investments are mostly from  investments.
Keywords: Responsible investment; the banking performance; small and medium banks